Association Between a History of Dengue Fever and the Risk of Systemic Autoimmune Rheumatic Diseases: A Nationwide, Population-Based Case-Control Study - Chen, Yun-Wen; Hsieh, Tsu-Yi; Lin, Ching-Heng; Chen, Hsian-Min; Lin, Chi-Chien; Chen, Hsin-Hua (Frontiers in Medicine, 2021)
Purpose To determine the association between a history of clinically diagnosed dengue infection and the risk of systemic autoimmune rheumatic diseases (SARD). Methods Using claims data from the 1997–2013 Taiwanese National Health Insurance Research Database, we included 74,422 newly diagnosed patients with SARD and 297,688 age/sex/index date/city of residence matched (1:4) non-SARD individuals as study subjects. The associations between the development of SARD and history of dengue infection (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] code 061) were investigated using conditional logistic regression analysis shown as odds ratios (ORs) with 95% confidence intervals (CIs) after adjusting potential confounders. Results SARD risk was significantly associated with prior history of dengue infection (OR, 1.53; 95% CI, 1.20–1.94; p = 0.001), especially in patients with systemic lupus erythematosus (SLE) (OR, 4.55; 95% CI, 2.77–7.46; p < 0.001). No association was found between dengue infection and Sjogren’s syndrome (SS) (OR, 1.41; 95% CI, 0.88-2.26; p = 0.155), rheumatoid arthritis (RA) (OR, 1.03; 95% CI, 0.70–1.50; p = 0.888), systemic sclerosis (SSc) (OR, 1.97, 95% CI, 0.38–10.29; p = 0.420), dermatomyositis (DM) (OR, 0.54, 95% CI, 0.04–7.27; p = 0.641) or polymyositis (PM) (OR, 2.08, 95% CI, 0.23–18.79; p = 0.513). Conclusion This nationwide, population-based study revealed a significant association between a history of dengue infection and the risk of SARD, in particular SLE.